Diffusion- and perfusion-weighted imaging in acute lacunar infarction: is there a mismatch? - Alex Förster; Hans Ulrich Kerl; Holger Wenz; Marc A Brockmann; Ingo Nölte; Christoph Groden (PLoS ONE, 2013)
PURPOSE:Characterization of lacunar infarction (LI) by use of multimodal MRI including diffusion- and perfusion-weighted imaging (DWI, PWI) is difficult because of the small lesion size. Only a few studies evaluated PWI in LI and the results are inconsistent. METHODS:In 16 LI patients who underwent initial MRI within 6 hours after symptom onset and follow-up MRI within 1 week demographics, clinical presentation, and MRI findings were analyzed with special emphasis on DWI and PWI findings. Time to peak maps were classified as showing a normal perfusion pattern or areas of hypoperfusion which were further categorized in mismatch (PWI>DWI), inverse mismatch (PWI<DWI), and match (PWI=DWI). Quantitative perfusion maps were generated and analyzed by use of Signal Processing in NMR-Software (SPIN). RESULTS:Of the 16 patients (mean age 65.5±12.9 years), 14 (87.5%) were male. Clinical symptoms comprised dysarthria (50%), hemiparesis (81.3%), and hemihypaesthesia (18.8%). Intravenous thrombolysis was performed in 7 (43.8%) patients. Clinical improvement was observed in 12 patients (75 %), while 2 (12.5%) patients showed a deterioration and another 2 (12.5%) a stable course. Acute ischemic lesions (mean volume of 0.46±0.29 cm³) were located in the thalamus (n=8, 50%), internal capsule (n=4, 25%), corona Radiata (n=3, 18.8%) and the mesencephalon (n=1, 6.3%). Circumscribed hypoperfusion (mean volume 0.61±0.48 cm³) was evident in 10 (62.5%) patients. Of these, 3 patients demonstrated a match, 4 an inverse mismatch, and 3 a mismatch between DWI and PWI lesion. Mean CBF and CBV ratios were 0.65±0.28 and 0.84±0.41 respectively. Growth of DWI lesions was observed in 7 (43.8%) and reversal of DWI lesions in 3 (18.8%) patients. CONCLUSIONS:MRI allows identification of different DWI and PWI patterns in LI, including growth and reversal of ischemic lesions. Consequently, it may serve for a better characterization of this stroke subtype and support treatment decisions in daily clinical practice.